Detection of Furcraea Necrotic Streak Virus (FNSV) in fique seed (Furcraea macrophylla Baker) to prevent the spread of the macana disease - Gamero, Maira (2023)
The fique crop has great potential for the development of the natural fiber market as a beneficial alternative for the protection of the environment. In Colombia, one of the main limitations of fiber production in fique plants is the viral disease Macana caused by Furcraea Necrotic Streak Virus (FNSV). This work aimed to validate the detection of FNSV in asexual planting material from one of the main producing areas and thus contribute to preventing the spread of the disease in the country. The analysis of plants from different geographic altitudes in Cauca, Colombia, showed a positive correlation with the prevalence of Macana disease (being more significant at higher altitudes) but not with the severity of the symptoms. The detection of FNSV on seeds by dot blot immunobinding assay (DBIA) using a polyclonal antibody IgY showed sensitivity (79 %) and specificity (80 %) when sprouts were analyzed, at the same time, for bulbils, the sensitivity was higher (100 %). Moreover, when sprouts were analyzed by the RT-PCR based on FNSV movement protein and polymerase-associated proteins, the sensitivity and specificity were 94 % and 50 %, respectively, in contrast, in the case of bulbils, the specificity was higher (100 %). Additionally, the results showed no uniformity in the distribution of the viral particles on vegetal tissue of infected plants, which is necessary to use the largest amount of tissue possible to perform the detection. As part of the optimization of the techniques, it was shown that plant tissue samples could be collected, transported, and stored on filter paper, allowing the detection of the virus 60 days after collection.